Accelerating burn wound healing using alginate/carboxymethyl cellulose nanogel containing Tussilago farfara and ZnO nanoparticle - kolarijani, Nariman Rezaei; Zamani, Sepehr; Gharibshahian, Maliheh; Aldaghi, Niloofar; Semyari, Hossein; Vaez, Ahmad; Rahmati, Majid; Sohrabi, Sina; Hedayat, Farhad; Gharravi, Anneh mohammad; Salehi, Majid (Burns, 2025)
The use of hydrogel-based drug delivery systems can help achieve the functional integrity of the skin after injury. This study focuses on preparing alginate/carboxymethylcellulose/zinc oxide nanoparticles/Tussilago farfara hydrogel and evaluates its regenerative effects on burn wounds. Zinc oxide nanoparticles (ZnONPs) act as an antibacterial agent, while Tussilago farfara (T. farfara) facilitates the wound healing processes. Characteristics of hydrogel treatment groups, in vivo studies, and histopathological evaluation were assessed 14 days after treatment. The hydrogels were fully characterized and tested in vitro and in a rat model for biocompatibility and wound-healing efficacy. The results showed a porous structure, favorable swelling and degradation rates, optimal blood compatibility and blood clotting index, and blood absorption capacity. Biocompatibility was confirmed by MTT assay. T. farfara/ZnONPs-containing hydrogels showed antibacterial activity against Staphylococcus aureus and Pseudomonas aeruginosa. The histopathological results showed more complete re-epithelialization and tissue regeneration compared to the other investigated groups. The initial outcomes suggest that the alginate/carboxymethylcellulose/ZnO/T. farfara hydrogel could be a good way to treat burn wounds, but more research is needed to confirm this. •Alginate/CMC/ZnO/TF hydrogel enhances burn healing via antibacterial/regenerative action.•Hydrogel shows optimal porosity, swelling, blood compatibility, and biocompatibility.•TF/ZnONP hydrogel combats S. aureus and P. aeruginosa, reducing burn infection risks.•In vivo: Accelerated re-epithelialization, and tissue regeneration in 14 days.•Multifunctional biocompatible hydrogel improves burn management and skin restoration.